2012
DOI: 10.1016/j.cub.2012.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Perceptual Learning in the Absence of Sensory Adaptation

Abstract: Repeated performance of visual tasks leads to long-lasting increased sensitivity to the trained stimulus, a phenomenon termed perceptual learning. A ubiquitous property of visual learning is specificity: performance improvement obtained during training applies only for the trained stimulus features, which are thought to be encoded in sensory brain regions [1-3]. However, recent results show performance decrements with an increasing number of trials within a training session [4, 5]. This selective sensitivity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
134
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 27 publications
(49 reference statements)
9
134
2
Order By: Relevance
“…The key elements of action video game play that lead to appreciable transfer of visual learning are not yet clearly understood. However, the varied perceptual demands in these tasks are congruent with many of the conditions that promote learning transfer on traditional perceptual learning paradigms (45)(46)(47)50). Musicianship represents yet another form of sensorimotor learning that shares a number of qualities with the auditory foraging game (e.g., audiomotor feedback that is both immediate and directional) and has recently been associated with generalized enhancement of auditory skills (18,19,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key elements of action video game play that lead to appreciable transfer of visual learning are not yet clearly understood. However, the varied perceptual demands in these tasks are congruent with many of the conditions that promote learning transfer on traditional perceptual learning paradigms (45)(46)(47)50). Musicianship represents yet another form of sensorimotor learning that shares a number of qualities with the auditory foraging game (e.g., audiomotor feedback that is both immediate and directional) and has recently been associated with generalized enhancement of auditory skills (18,19,51).…”
Section: Discussionmentioning
confidence: 99%
“…Learning transfer to a more complex signal in noise task was surprising given that stimulus specificity has been repeatedly associated with sensory learning since the seminal report of Fiorentini and Berardi (42) over 3 decades ago. However, recent studies have cast doubt on the inviolate specificity of perceptual learning, suggesting that the particular training methodology may influence the degree of learning transfer (43)(44)(45)(46)(47)(48). For example, experience with action video games has been associated with accelerated learning of nonnative phonetic contrasts (49) and enhanced visual abilities on tasks ranging from useful field of view to contrast sensitivity (20,21,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, recent work on non-linguistic sensory adaptation (mostly in lowlevel vision and audition) has revealed that many negative aftereffects which were originally attributed to the fatigue of neuronal feature detectors are better explained by neural populations adjusting their processing to maximize the transmission of information about the current stimulus ensemble (Brenner et al, 2000;Fairhall et al, 2001;Gutfreund, 2012;Kohn, 2007;Sharpee et al, 2006;Webster et al, 2005), which parallels recent developments in the understanding of perceptual learning in low-level perceptual tasks (Bejjanki, Beck, Lu, & Pouget, 2011;Harris, Gliksberg, & Sagi, 2012). Maximizing information transmission depends on the statistics of the environment at many different levels.…”
Section: Discussionmentioning
confidence: 85%
“…In the present study, perceptual learning was observed only in the location in which the trained stimulus was presented. However, in some cases, perceptual learning is transferred to untrained visual field locations (7,8). Second, would similar results be observed in perceptual learning of other sensory features and its transfer?…”
mentioning
confidence: 87%
“…More recently, it has been found that, if some methods are combined with traditional training methods of perceptual learning, perceptual learning of a stimulus at a location in the visual field is transferred to other locations (7,8). These findings have attracted a great deal of attention because they suggest that neural sites involved in perceptual learning include brain regions beyond early sensory areas.…”
mentioning
confidence: 99%